2023
DOI: 10.1098/rstb.2022.0024
|View full text |Cite
|
Sign up to set email alerts
|

Molecular elements: novel approaches for molecular building

Abstract: Classically, a molecular element (ME) is a pure substance composed of two or more atoms of the same element. However, MEs, in the context of this review, can be any molecules as elements bonded together into the backbone of synthetic oligonucleotides (ONs) with designed sequences and functions, including natural A, T, C, G, U, and unnatural bases. The use of MEs can facilitate the synthesis of designer molecules and smart materials. In particular, we discuss the landmarks associated with DNA structure and rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 137 publications
0
7
0
Order By: Relevance
“…In addition, it appears that ALIEN DNA can adopt a wider range of Bform structures than DNA constructed with only Watson-Crick nucleobases. Numerous studies have shown that the presence of non-canonical nucleobases can improve the ability of aptamers to bind to their cellular targets and the implications of these observations for nanotechnology and the development of nucleic acid therapeutics are summarized in an opinion piece by Wang et al [27] These authors point out the large chemical diversity of aptamers and the fact that base-pairing can be exploited to control their threedimensional structure in a precise manner. These ideas are well illustrated in the subsequent research article by Kimoto et al [28] who exploit a different type of non-canonical nucleobase, which is hydrophobic and lacks hydrogen bonding groups (figure 4), to obtain aptamers with improved affinities and selectivities.…”
Section: Expanding the Genetic Alphabetmentioning
confidence: 99%
“…In addition, it appears that ALIEN DNA can adopt a wider range of Bform structures than DNA constructed with only Watson-Crick nucleobases. Numerous studies have shown that the presence of non-canonical nucleobases can improve the ability of aptamers to bind to their cellular targets and the implications of these observations for nanotechnology and the development of nucleic acid therapeutics are summarized in an opinion piece by Wang et al [27] These authors point out the large chemical diversity of aptamers and the fact that base-pairing can be exploited to control their threedimensional structure in a precise manner. These ideas are well illustrated in the subsequent research article by Kimoto et al [28] who exploit a different type of non-canonical nucleobase, which is hydrophobic and lacks hydrogen bonding groups (figure 4), to obtain aptamers with improved affinities and selectivities.…”
Section: Expanding the Genetic Alphabetmentioning
confidence: 99%
“…As it is often the case, a limitation to the state of the art is posed by the fact that it has been conducted mainly in Western, so-called WEIRD countries (Henrich, Heine and Norenzayan, 2010), except for at least four studies (known to us) run in China (Dong et al, 2021;Kline et al, 2018;Wang et al, 2023;Wang et al, 2020). When it comes to understanding the worldwide willingness to cooperate in global issues like climate change, it is necessary to examine the replication of findings in Eastern countries, especially those that have been harshly impacted by environmental issues in recent years due to a delayed industrial revolution.…”
Section: Cooperative Behaviour and Collectivistic Valuesmentioning
confidence: 99%
“…30 This approach offers a modular and highly adaptable platform for the synthesis of functional oligonucleotides by a DNA synthesizer machine. 31 We hypothesize that PTE can serve as a qualified pharmaceutical element within ONs, so the potential of PTE would be unlocked by targeted delivery using an aptamer-based nanomedicine (Scheme 1). Herein, we present the results of PTE phosphoramidite synthesis and the preparation of an aptamer−PTE conjugate.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Pharmaceutical elements can be integrated into ApDCs in a manner similar to natural elements A, T (U), C, and G, employing corresponding phosphoramidites . This approach offers a modular and highly adaptable platform for the synthesis of functional oligonucleotides by a DNA synthesizer machine . We hypothesize that PTE can serve as a qualified pharmaceutical element within ONs, so the potential of PTE would be unlocked by targeted delivery using an aptamer-based nanomedicine (Scheme ).…”
Section: Introductionmentioning
confidence: 99%